Communicology: old commitments, traditional science and critical perspective / La comunicología: viejos compromisos, ciencia tradicional y perspectiva crítica - Rainer Rubira García; Belén Puebla Martínez; Elena Carrillo Pascual (Barataria, 2013)
This text deals, from a critical and historical perspective, with the shaping processes of the communication sciences academic field, taking into account the particularities of the context in which the discipline emerged. From the study of different opposing epistemological perspectives within Communication, as a research area still in the process of articulation, the need to strengthen a critical approach in the scientific praxis of the agents in charge of reproducing the field is encouraged. The significance to understand communicative interchanges in their social and humanistic dimension, from a critical point of view, as well as their transformative value, as a way of contributing to the enrichment of individuals and society to which they belong, is one of the main elements in discussion in this article.